2022
DOI: 10.1002/mp.15717
|View full text |Cite
|
Sign up to set email alerts
|

Design of static and dynamic ridge filters for FLASH–IMPT: A simulation study

Abstract: Purpose This paper focused on the design and optimization of ridge filter–based intensity‐modulated proton therapy (IMPT), and its potential applications for FLASH. Differing from the standard pencil beam scanning (PBS) mode, no energy/layer switching is required and total treatment time can be shortened. Methods Unique dose‐influence matrices were generated as a proton beam traverses through slabs of different thicknesses (i.e., modulation by different layers). To establish the references for comparison, conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
(103 reference statements)
0
24
0
Order By: Relevance
“…The base of the range modulator is shaped to act as a range compensator to match the distal contour of the tumor. It has been shown that this set-up could easily achieve dose rate of at least 40 Gy/s [18,7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The base of the range modulator is shaped to act as a range compensator to match the distal contour of the tumor. It has been shown that this set-up could easily achieve dose rate of at least 40 Gy/s [18,7].…”
Section: Introductionmentioning
confidence: 98%
“…To plan a conformal PBS FLASH treatment it is therefore necessary to optimize a patient-specific range modulator and the weights of the PBS spots. Several methods have already been proposed [13,7,18]. Although different, they are based on two common principles:…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches have been proposed for FLASH planning using spread-out single-energy proton beams, in which patient-specific range compensators were used to pull back the BPs to the target exit edge and pin-shaped ridge filters (RFs) were customized to spread out the BPs to the proximal edge of the target. [24][25][26] Nevertheless, either using the customized range compensators alone or combining the patient-specific pin-shaped RFs and range compensators for FLASH planning has limitations in adapting to patient anatomical changes that often occur during the treatment courses, such as tumor regression, since a time-consuming process for re-making the range compensators and/or pin-shaped RFs may be required.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the uniform range shifters (RSs) and patient‐specific universal range compensators were employed to align the BPs of the high‐energy proton beams to the distal edge of the target from multiple beam directions, which demonstrated improved OAR sparing with sufficient target dose coverage and comparable FLASH dose rate coverage compared to the TB‐only planning. Alternative approaches have been proposed for FLASH planning using spread‐out single‐energy proton beams, in which patient‐specific range compensators were used to pull back the BPs to the target exit edge and pin‐shaped ridge filters (RFs) were customized to spread out the BPs to the proximal edge of the target 24–26 . Nevertheless, either using the customized range compensators alone or combining the patient‐specific pin‐shaped RFs and range compensators for FLASH planning has limitations in adapting to patient anatomical changes that often occur during the treatment courses, such as tumor regression, since a time‐consuming process for re‐making the range compensators and/or pin‐shaped RFs may be required.…”
Section: Introductionmentioning
confidence: 99%
“…However, such SOBP delivery can hardly reach the dose rate of FLASH RT mainly because: first, the beam current decreases dramatically as proton energy decreases due to beam transmission efficiency loss in the energy selection system 22,23 ; second, the typical energy switch time is ∼900 ms for energy degradation‐based cyclotron systems 24 and on a scale of >1000 ms for synchrotron systems, 25 which also prolongs the beam‐on time. Ridge‐filter‐based SOBP 26 and compensator‐based single‐energy Bragg peak 15 delivery techniques were proposed to improve the dose rate by eliminating the necessity of energy switching while maintaining dose conformity compared to transmission delivery. However, high‐energy transmission delivery, which is characteristic of high current and less sensitivity to range uncertainties, is more practical to accommodate FLASH dose rates to be used for preclinical studies on animals 14,27,28 .…”
Section: Introductionmentioning
confidence: 99%